PHYSICAL DISABILITIES IN LEPROSY: CHARACTERIZATION, FACTORS RELATED AND EVOLUTION - Gabriela de Cássia Ribeiro; Francisco Carlos Félix Lana (Universidade Federal do Paraná, 2015)
The aim of this study was tocharacterize the new cases of leprosy; analyze socioeconomic, demographic, clinical-epidemiological, and access to diagnosis and treatment aspects related to the occurrence of leprosy with physical disabilities; and analyze the development of disabilities during treatment.A retrospective cohort survey was conducted in the health region of Diamantina, Minas Gerais, Brazil. One hundred seven reports of leprosy and 71 interviews were analyzed between 2005 and 2010. The most frequent diagnoses were multibacillary (73.2%) and physical disability (79.1%). There was a statistical relationship between the development of physical deformities and those affected by leprosy with lower levels of schooling, higher neural involvement, and greater difficulties in accessing the health unit, in addition to the maintenance of the degree of disability. There is a reduced operational capacity of the Family Health Strategy (FHS) regarding leprosy control actions and the need to implement the policy according to the Unified Health System (SUS, from its acronym in Portuguese).